PENGARUH MANAJEMEN KEPALA MADRASAH TERHADAP KUALITAS PENDIDIKAN (PENELITIAN PADA MADRASAH ALIYAH NEGERI SIBOLGA) - Sihombing, Irwandi (AIN Padangsidimpuan, 2016)
Management of education is a major resource for the advancement of a nation, for that education needs to be built and developed to be capable in producing superior human resources, advanced and competitive. The function of education is strategically most important for a nation, especially the people who carry out development should optimalize education system functions to deliver the human resources of high quality as the organizer of development and in order to improve the quality of life of the community, the nation and the state. Management of headmaster in improving the quality of education in Madrasah Aliyah Negeri Sibolga must strive to increase the quality of education, including the quality of the performance and management of headmaster, deputy, teachers and committee of Madrasah to provide and support to all stakeholders of education in madrasah as a systematically, integratedly, well-planned and professionally. In order to achieve an effective and efficient organization, management must be enabled fully to every organization including education. The management functions as planningÂ organizing, implementation, monitoring and evaluation.